Peran efikasi diri dalam memediasi interaksi mindfulness dan burnout pada guru sekolah dasar inklusif - G.D., Putu Winda Yuliantari; Widyasari, Pratiwi (Persona:Jurnal Psikologi Indonesia, 2020)
AbstractThe role of teachers, especially in primary school education, is something that needs to be considered as a form of anticipation of emotional fatigue that results in burnout. This study aimed to examine the effect of teacher self-efficacy in mediating the relationship of mindfulness to the domain of burnout conditions. Data collected from participants in inclusive primary school (n = 174) using convenience sampling techniques. This study used Mindfulness in Teaching Scale, Teacher Efficacy in Inclusive Practice, and Maslach Burnout Inventory-Educator Survey as measuring tools, which has been adapted to the context of inclusive education in Indonesia. The results of the regression test and the Sobel test showed that self-efficacy significantly mediates the relationship between mindfulness conditions and the domain of personal achievement in burnout conditions. The teacher's self-efficacy becomes an important thing to consider when wanting to handle mindfulness in helping to improve the domain of personal accomplishment in burnout conditions. Implications, limitations of the study, and suggestions for further research are discussed.Keywords: Burnout; Inclusive education; Mindfulness; Primary school teacher; Self-efficacy  AbstrakPeran guru terutama di pendidikan sekolah dasar menjadi hal yang perlu untuk diperhatikan sebagai bentuk antisipasi terhadap kondisi kelelahan emosional yang berujung pada burnout. Penelitian ini bertujuan menguji pengaruh efikasi diri guru dalam memediasi hubungan kondisi kesadaran (mindfulness) terhadap domain kondisi burnout. Pengambilan data partisipan penelitian di sekolah dasar inklusif (n=174) dilakukan dengan teknik convenience sampling. Penelitian ini menggunakan alat ukur Mindfulness in Teaching Scale, Teacher Efficacy in Inclusive Practice, dan Maslach Burnout Inventory-Educator Survey, yang telah diadaptasi ke dalam konteks pendidikan inklusif di Indonesia. Hasil uji regresi dan uji Sobel menunjukkan efikasi diri secara signifikan memediasi hubungan antara kondisi mindfulness dengan domain pencapaian personal pada kondisi burnout. Efikasi diri guru menjadi hal yang penting untuk diperhatikan ketika ingin melakukan penanganan terhadap kondisi kesadaran (mindfulness) dalam membantu meningkatkan domain pencapaian personal pada kondisi burnout. Implikasi, keterbatasan penelitian, dan saran untuk penelitian selanjutnya didiskusikan.Kata kunci: Burnout; Efikasi diri; Guru sekolah dasar; Mindfulness; Pendidikan inklusif